Emerging and re-emerging natural focal diseases of European Russia (typological classification of nosological profiles and dynamics of incidence) - Svetlana M. Malkhazova; Polina V. Pestina; Vladimir S. Tikunov (Geography, Environment, Sustainability, 2020)
This study considers an automated typological classification version by using the extensive factual material in analysis of emerging and re-emerging natural focal diseases of European Russia.The typological classification of nosological profile (a set of diseases) and the incidence dynamics for five nosological forms (hemorrhagic fever with renal syndrome, ixodic tick-borne borreliosis, tick-borne encephalitis, tularemia, and leptospirosis) was created using the formal methods of mathematical-cartographical modeling. This classification of the incidence in 1997–2015 yielded five types of the nosological profiles. These types vary by years, which is associated with the dependence of the incidence on climatic conditions in each specific year and on extent of deratization and preventive measures. The results obtained can be used to forecast potential epidemiological outbreaks and to develop targeted and appropriate for each region measures.